The tools for city centre revitalization in Portugal - Guimarães, Pedro Porfírio (2018)
Purpose – The purpose of this article is to critically review some interventions made in Portugal through Commercial Urbanism Programmes. These public interventions, with the objective of revitalizing city centres and modernizing the retail sector, culminated with the development of town centre management schemes. The paper also intends to analyze how these interventions have been evaluated. Design/methodology/approach – The paper contains a brief literature review which clarifies why city centres went into decline and why we should apply positively discriminatory policies in order to revitalize them. Second, the paper describes the main aspects of the public programmes and town centre management in the Portuguese context. After, the paper identifies the main aspects that concern the evaluation of impacts. The paper approaches the difficulties, gaps and importance of evaluation. In the last point the paper draws some final considerations. Findings – This research identifies the main measures implemented in Portugal in order to overcome the decline felt in city centres. Also it recognizes some gaps in the interventions, mainly regarding the lack of concern for local specifications. It also recognizes the difficulty in establishing a proper evaluation and identifies different ways of collecting data, usable for an evaluation. Originality/value – This paper helps clarify the process of public intervention in city centres in Portugal. Beside that it sheds somelight about the importance of evaluation and howdata can be collected.